MIXED GAS-OIL SUBSEA PIPELINES IN OFFSHORE TECHNOLOGY: TECHNICAL AND ECONOMIC ASPECTS - Caputo, A. C.; Pelagagge, P. M.; Ponticiello, I. (Revista de Engenharia Térmica, 2004)
The choice of gas separation and transportation mode in offshore applications may significantly affect the project profitability. Main alternatives are separation on board the platform with the utilization of separate subsea pipeline for single-phase gas and oil transportation, and remote separation with multiphase transportation of the gas-oil mixture in a single pipeline. In order to assist the project engineers during the feasibility study phase, the problems relevant technical and economic issues are analysed in this paper after preliminarily describing the two process schemes. In particular a computer model is developed in order to simulate the two-phase flow of the multi-component mixture adopting the Beggs and Brill model, which showed to be the most reliable approach in this application. A cost comparison with reference to a hypothetical but realistic case study is finally carried out to assess the convenience of the multiphase flow solution. This option appears to be especially attractive when multiplewell fields exist which can be developed in an integrated manner by providing a single centralized separation plant. A Allowance for additional mass (t) L Liquid production (m3/day x 1000) STP Standard Temperature and Pressure